2002
DOI: 10.1128/aac.46.5.1561-1563.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacodynamics of Three Newer Fluoroquinolones versus Six Strains of Staphylococci in an In Vitro Model under Aerobic and Anaerobic Conditions

Abstract: Six strains of staphylococci were exposed to levofloxacin, moxifloxacin, or trovafloxacin in an in vitro pharmacodynamic model under both aerobic and anaerobic conditions. Each agent demonstrated a rapid 3-log 10 kill versus susceptible isolates regardless of condition. Against clinical isolates with reduced susceptibility, regrowth occurred by 24 h and was frequently associated with further increases in MICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…Overall, only 30 to 50% of the observations in these studies provided useful information. It is fair to say that similar problems also were inherent in more rigorously designed dose (AUC/MIC)-ranging studies (17,18,25,27,33). For example, in studies where S. pneumoniae (17), B. fragilis (25), and Bacteroides thetaiotamicron (27) were exposed to wide ranges of quinolone AUC 24 /MIC values, quantitative data could be obtained in only 10 to 66% of experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, only 30 to 50% of the observations in these studies provided useful information. It is fair to say that similar problems also were inherent in more rigorously designed dose (AUC/MIC)-ranging studies (17,18,25,27,33). For example, in studies where S. pneumoniae (17), B. fragilis (25), and Bacteroides thetaiotamicron (27) were exposed to wide ranges of quinolone AUC 24 /MIC values, quantitative data could be obtained in only 10 to 66% of experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Agents Chemother., poster A-440, 2001). Despite wide ranges of AUC/MIC ratios simulated in some recent studies (17)(18)(19)(20)27,33; MacGowan and Bowker, 41st ICAAC), reasonable relationships with resistance were not established. The relatively few studies of these relationships can be classified as those that directly attempt to relate resistance to the simulated pharmacokinetics but do not (17,20) and those that imply the existence of relationships with the AUC/MIC ratio measured within a 24-h dosing interval (AUC 24 /MIC) or with the C max /MIC ratio but do not actually report them (26,27,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gli studi effettuati con modelli in vitro hanno dimostrato che la moxifloxacina è dotata di un elevato potere battericida nei confronti dei ceppi sensibili [65][66][67][68][69][70][71][72][73][74] .…”
Section: Farmacodinamicaunclassified
“…The maximum antibacterial effects and the AUC/MIC ratios for various effects were similar in aerobic and anaerobic conditions. This builds on the earlier work of Wright et al (24), who showed that levofloxacin, trovafloxacin, and moxifloxacin were rapidly bactericidal against staphylococci in an in vitro model, irrespective of aerobic or anaerobic growth conditions.…”
Section: Micsmentioning
confidence: 99%